Aplikasi Simplex Lattice Design untuk Optimasi Emulgator dalam Krim Minyak Atsiri Kulit Jeruk Manis - Pratiwi, Puspa Dwi; Arnas, Deah Lestiana (Sinteza, 2024)
In order to obtain a perfect emulsified and stable preparation, choosing the right composition emulsifier is crucial. Formula optimization is needed to determine the best combination of ingredients in formulation process based on evaluation responses. Simplex Lattice Design (SLD) is an experimental design method for mixing materials with the proportion of the total number of materials 1 or 100%. This research was aims to obtained the optimal cream formula using tween 80 and span 80 as emulsifiers and determined their effect on the physical properties of cream preparation. SLD method was used as optimization method with tween 80 and span 80 as independent variables and pH, viscosity, spreadability, and stickiness as responses. The minimum limit for tween 80 and span 80 is 1% (w/v) and the maximum is 9% (w/v) with total 10%. The optimal formula was obtained from consideration of the response by entering the target value to obtain a formula with desirability value close to 1. There are 5 formulas based on SLD recommendations, with a concentration ratio of tween 80 and span 80 9:1 (run 1); 7:3 (run 2); 1:9 (run 3); 5:5 (run 4); and 3:7 (run 5). The relationship between concentration and response value can be explained based on the significance of the model and equations obtained. The optimal formula was the concentration ratio of tween 80 and span 80 8.6:1.34 with a desirability value of 0.953. The conclusion of this research was that SLD can be used to optimize the emulsifier with response predictions close to the results obtained.